Treatment of varicose great saphenous veins with saphenofemoral junction insufficiency – what is the evidence? - Holzheimer, René Gordon; Obermayer, Alfred; Noppeney, Thomas (Phlebologie, 2020)
The results of studies on treatment of the great saphenous vein (GSV) with sapheno-femoral-junction (SFJ) insufficiency are unclear. Guidelines, however, recommend endovenous laser ablation (EVLA) and ultrasound-guided-foamsclerotherapy (UGFS) for symptomatic varicose large saphenous vein. There are numerous studies on GSV treatment but only a few randomized studies with a follow-up of two years and more. Meta-analyses in most instances included all studies and do not focus on studies with a follow-up of two years and longer.Methods A literature research in Pubmed used the keyword “great saphenous vein treatment”, “large saphenous vein treatment”, “varicose therapy” in conjunction with “randomized controlled trial”, “meta-analysis” and “systematic review”. Of 128 studies only 24 randomized controlled studies investigated the effect of High Ligation and Continuous Stripping (HL + CS), Endovenous Laser Ablation (EVLA), Radiofrequency Ablation (RFA), Liquid Sclerotherapy (LS), and Ultrasound-Guided-Foam-Sclerotherapy (UGFS) and a follow-up of two and more years. Study evaluation included “reflux”, “recurrence”, “therapy technique”, numbers of patients/legs treated, length of follow-up, and primary/secondary study endpoints.Results Most of these studies investigated surgical High Ligation and Continuous Stripping (HL + CS) with a follow-up of two years and more. This technique served a reference technique for other techniques in randomized controlled studies. However, there are major differences in techniques, mode of treatment, definitions, criteria for exclusion and inclusion, and study endpoints.The surgery study group included 1915 legs in 19 studies, the EVLA group 1047 legs in 12 studies and 240 legs in 3 studies with combined HL + EVLA treatment. RFA was used in 299 legs in 4 studies, UGFS in 661 legs in 5 studies, combined UGFS + HL in 39 legs and LS + HL in 92 legs in one study each.EVLA is associated with more reflux and recurrence when compared to HL + CS. RFA shows similar reflux and recurrence rates as surgery. In most studies UGFS and LS is followed by more reflux and recurrence when compared to surgery.Conclusion Due to heterogeneity of studies comparing study results of HL + CS, EVLA, RFA, LS and UGFS is not reliable. UIP or ECOP may form a commission to establish uniform, reliable and accepted study designs for varicose vein treatment to improve comparability of further randomized studies.Die Studienlage zur Behandlung der insuffizienten Vena saphena magna (VSM) mit Mündungsklappeninsuffizienz ist unklar. Leitlinien empfehlen die Behandlung der Vena saphena magna mit chirurgischer Therapie, endovenös thermischen Ablationsverfahren oder ultraschallgestützter Schaumsklerosierung. Es gibt zahlreiche Studien der Behandlung der Vena saphena magna, aber nur wenige Studien sind randomisiert und haben ein längeres Follow-up als 2 Jahre. Metaanalysen haben meist alle Studien eingeschlossen und sich nicht auf Studien mit einem Follow-up von mehr als 2 Jahren beschränkt.Methodik In einer Literaturrecherche über Pubmed wurden die Keywords „great saphenous vein treatment“, „large saphenous vein treatment“, „varicosis therapy“ in Verbindung mit „randomized controlled trial“, „meta-analysis“ und „systematic review“ erfasst. Es wurden 128 Studien gefunden, davon 24 Studien seit 1990 zur Behandlung der Vena saphena magna mit offener Chirurgie, Crossektomie und Stripping, Hohe Ligatur plus Stripping (HL + CS), endovenöser Laserablation (EVLA), Radiofrequenzablation (RFA), flüssiger (LS) oder Schaumsklerosierung (FS) sowie ultraschallgestützter Schaumsklerosierung (UGFS) mit einem „Follow-up“ von mehr als 2 Jahren. Die Studien wurden nach „Reflux“ und „Rezidiv“ hinsichtlich Therapietechnik, Patientenzahl, Länge des Follow-ups sowie der Angabe primärer und sekundärer Endpunkte ausgewertet.Ergebnis Die meisten Studien mit einem längeren Follow-up (≥ 2 Jahre) liegen für chirurgische Verfahren „Hohe Ligatur und konventionelles Stripping“ (HL + S), aus dem Englischen für Crossektomie, vor. HL + S ist die Referenzmethode gegenüber den anderen Therapietechniken. Es bestehen erhebliche Unterschiede in Technik, Ausführung der Behandlung, Definitionen, Ein- und Ausschlusskriterien sowie Studienendzielen. Die chirurgische Gruppe bestand aus 1915 behandelten Beinen in 19 Studien. In der EVLA-Gruppe wurden 1047 Beine mit EVLA-Monotherapie in 12 Studien und 240 Beine mit HL + EVLA in 3 Studien behandelt und ausgewertet. 299 Beine in 4 Studien wurden mit RFA behandelt. In der UGFS-Gruppe wurden 661 Beine in 5 Studien behandelt. 39 Beine wurden kombiniert mit UGFS + HL und 92 Beine kombiniert mit LS + HL in jeweils 1 Studie behandelt.Im Vergleich zu HL + S weisen die Studien mit EVLA mehr Reflux und Rezidive auf, Studien mit RFA hingegen zeigen bei Reflux und Rezidiven kaum Unterschiede. Studien zur Flüssigsklerosierung (LS), Schaumsklerosierung und (FS) ultraschallgestützten Schaumsklerosierung (UGFS) weisen wesentlich schlechtere Ergebnisse als die Studien der chirurgischen und endovenösen Behandlung auf.Schlussfolgerung Aufgrund der Heterogenität der aufgeführten Studien sind verlässliche Aussagen zu HL + S, EVLA, RFA und LS/UGFS unter den angegebenen Bedingungen nicht möglich. UIP oder ECOP sollten eine Kommission gründen, die für varizenausschaltende Eingriffe ein verbindliches Studiendesign definiert, um für zukünftige Studien eine bessere Vergleichbarkeit der Ergebnisse zu ermöglichen.
Keywords: great saphenous vein; high ligation and continuous stripping; endovenous laser ablation; radiofrequency ablation; foam sclerotherapy